Web Based Fosti Information System at Muhammadiyah University of Surakarta - Nendy Akbar Rozaq Rais; Aini Zahra (Institut Teknologi Bisnis AAS Indonesia, 2020)
Abstract—The student unit activity is an institution to achieve goals by holding events within the institution. FOSTI is one of the student activity units on the campus of the Muhammadiyah University of Surakarta that uses a web-based information system, of course in this application to make it easier to collect data or register for events being held. The purpose of this final semester assignment is to find out how to make or design an application system and train to analyze the existing system and evaluate the deficiencies in the system to the user. The registration process for event participants is done manually, often incorrectly in recording or data collection of event participants and creating piles of data in the form of papers, allowing data to be inserted due to negligence on the part of the committee. To solve this problem, it is necessary to have a registration application system. Making this system using the framework system Laravel Based Framework. Used to find easy alternatives. The method in this management information system uses Laravel Based. Making a system in a program with the PHP programming language, the process of registering events held by the laravel based method can facilitate the registration and data collection process, which previously used the manual method which took quite a long time. The method in this research uses the method of observation, interviews, and literature study. for designing the system using Contex Diagram, HIPO, and DAD. The purpose of this study is to find out how to make or design an application system and train to analyze existing systems and evaluate the deficiencies of the system to the user. The final result in the registration process and event data collection is in the form of types of events in the FOSTI organization, Muhammadiyah University of Surakarta and participant data reports.